A Review of Codes and Standards for Bamboo Structural Design - Ermias A. Amede; Ezra K. Hailemariama; Leule M. Hailemariam; Denamo A. Nuramo (Advances in Materials Science and Engineering)
Bamboo is a strong, fast-growing, and sustainable material. In modern times, it can be an aesthetically pleasing and low-cost alternative to more conventional materials. Despite the literature’s consideration of bamboo’s promising potential as a resilient, sustainable building material for structural element design, its application is limited. This is mainly due to the limited availability of universally applicable standards and codes to guide or assist in developing the structural element design. As a result, bamboo as an engineering material was mainly dependent on established practical traditions, intuitions of forbears, and engineering experience. This paper reviewed available structural element design standards and codes of practice. Based on the literary works, it was possible to conclude that there is a need to develop a comprehensive universally applicable bamboo design, construction standards, and code of practices, addressing several social and trade benefits as well as engineering recognition and enhanced status of bamboo as an engineering material.